Circular Economy in Indonesia: A Comparative Study of EU Countries and Finland - Davy Parsaoran Hinsa; Oskar Ezra; Ratlan Pardede (Publikasi Indonesia, 2025)
The circular economy has become an alternative paradigm to support sustainable economic growth to address the challenges of natural resources and environmental impacts of the linear economic model. This study aims to analyze the potential of the circular economy in supporting the 8% economic growth target in Indonesia based on government policies, by comparing the European Union (EU) and Finland as a reference for developed countries. A qualitative approach is used through the analysis of policy documents such as Indonesia's National Medium-Term Development Plan (RPJMN) 2020-2024, the EU's Circular Economy Action Plan (CEAP) 2020, and Finland's National Circular Economy Roadmap, as well as secondary data and literature reviews from academic sources and official reports. The results show that Indonesia has great potential in the circular economy, with a projected contribution to the Gross Domestic Product (GDP) of (42-45) billion USD and the creation of 4.4 million jobs by 2030. However, its implementation lags far behind the EU and Finland in terms of efficiency and economic output. Indonesia only achieved a recycling rate of 15%, while the EU recorded 48.6% and Finland 43%. The contribution of the circular economy to Indonesia's GDP is projected to be only (2.2-2.3%), far from the target of 8%, compared to the EU (10.6%) and Finland (10%). This gap is caused by limited infrastructure, weak regulations, and a lack of technological innovation in Indonesia. The EU excels with structured policies and systemic coordination, while Finland excels in technological innovation albeit on a small scale.